Response to bolus methylprednisolone in Pulmonary Leptospirosis: Case Report - Ghimire, Amrit; Thapa, Sanjay Raj (Grande Medical Journal, 2025)
Pulmonary complications in leptospirosis are often unrecognized in a non-endemic area. We report here a patient with leptospirosis and severe pulmonary involvement who was treated with corticosteroids. This case report shows the beneficial effect of methylprednisolone in pulmonary leptospirosis, which usually has an aggressive course and grave outcome.